O percurso do agir interacional no trabalho docente: do projeto de ensino às participações contingentes em sala de aula de língua inglesa - Malabarba, Taiane (Universidade do Vale do Rio dos Sinos, 2015)
This research investigates classroom teaching as a practice understood here as real-concrete work. The main objective is to describe how, from the linguistic-interactional point of view, a teaching project is enacted in face of interactional contingencies. The study draws upon transcriptions of 10 (classroom) hours of video recordings generated with a group of elementary students in a private language school setting in the Southern region of Brazil. The focus of analysis were the moments when the course of actions changes due to unexpected student participations, so understood either because they were not pre-allocated by the teacher or because they fail to meet the expectations projected by a previous action. Concepts derived from Sociodiscursive Interactionism (BRONCKART, 1999) and Conversation Analysis (SACKS; SCHEGLOFF; JEFFERSON, 1974) in a broader perspective, which views talk-in-interaction as created through several semiotic fields (GOODWIN, 2013), were used as theoretical and methodological reference in the analysis. The findings reveal a pervasive route concerning talk-in-interaction observed in the accomplishment of the work of teaching: 1) teaching project; 2) unexpected participation; 3) alignment; 4) inner-expansion of the teaching project; 5) closing; and 6) teaching project among other less frequent routes. Altogether, the analysis accomplished reveal the constant interweaving movement between ordinary and institutional talk. Concerning the former, the presence of laughter, more relaxed body postures and specific prosodic features, which seem to be linked to the establishment of rapport with the students, is noticeable. Concerning the latter, attention is drawn to more straight body posture accompanied by a significant change in voice volume and/or pitch and an apparent reluctance in using Portuguese to interact with students. Such findings may contribute to the body of language classroom research by unveiling the actions that involve moments when the teaching project is reshaped due to interactional contingencies and by proposing the construction of a language for talking about teaching practice. Likewise, they may be used in teacher education programs in order to promote reflection and support the creation of a sustainable repertoire of interactional teaching practices to be used principally by novice teachers.
Keywords: Sala de aula de língua inglesa; Trabalho docente; Fala-em-interação; Participações contingentes; EFL classroom; The work of teaching; Talk-in-interaction; Contingent participations; ACCNPQ::Lingüística, Letras e Artes::Lingüística